PENGARUH PENAMBAHAN SEMEN, ABU SEKAM, DAN SERAT FIBER TERHADAP PENINGKATAN KUAT GESER TANAH LEMPUNG - Indrayani Indrayani .; Andi Herius; Alfin Ashadiq; Egal Hardewo; Arpan Hasan; Norca Praditya; Darma Prabudi (FROPIL (Forum Profesional Teknik Sipil), 2022)
Soil is an important element in supporting development activities in the world of civil construction. One type of soil that is often found in South Sumatra is clay. Clay soil is a type of fine-grained soil that is strongly influenced by water content. Each clay has a different carrying capacity value, therefore an analysis is needed to test the effect of adding a mixture of materials to the clay. To see the effect of adding mixed materials to the soil, a test was carried out, in this test soil samples were taken from the Banyuasin district and added mixed materials in the form of fiber, husk ash and cement. For variations in soil mixture testing, 0.1% fiber, 2.5% husk ash and cement consist of 2.5%, 5% and 7.5% as well as plain water. The test results show that the addition of a mixture of fiber, husk ash and cement can improve the physical and mechanical properties of clay. For testing of physical and mechanical properties, where the cohesion value increased with the addition of 7.5% cement of 43.78 Kpa with a shear angle of 17.30o.